The Canggha Agung Tradition as a Pre-Wedding Ceremony in West Kalianget Village, Sumenep Regency - Achmad Fathoni; Abdul Mukti Thabrani; Ahmad Yahya Wijaya; Moh. Qashdi (Faculty of Shariah UIN Ponorogo, 2025)
The canggha agung tradition is a pre-marriage ceremony that has been passed down from generation to generation in Kalianget Barat Village, Sumenep, Madura. This tradition is believed to ensure the smooth running of the marriage ritual. This study aims to identify the factors that support the preservation of this tradition and its relationship with the success of marriage. The research method used is descriptive qualitative, involving in-depth interviews with families who practice the canggha agung tradition, religious leaders, community leaders, and the general population of Kalianget Barat Village. Data was collected through interviews and supporting documents. The results of the study indicate that the preservation of the canggha agung tradition is supported by three main factors, namely (1) the community's belief in traditional values as a sacred heritage; (2) the empirical experience of couples who have undergone the tradition, who generally report a more harmonious household life; and (3) collective support from the community, including religious leaders and traditional elders. This tradition also serves as a medium to strengthen religious and spiritual values and enhance social solidarity among community members. The contribution of this research lies in its efforts to preserve local cultural heritage within the context of marriage, as well as providing a deeper academic understanding of the relationship between traditional customs and family resilience.